2021
DOI: 10.1002/sctm.21-0107
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Vesicles from Adipose Tissue- and Bone Marrow-Mesenchymal Stromal Cells in Endothelial Proliferation and Chondrogenesis

Abstract: The secretome of mesenchymal stromal cells (MSCs) derived from different tissue sources is considered an innovative therapeutic tool for regenerative medicine.Although adipose tissue-and bone marrow-derived MSCs (ADSCs and BMSCs, respectively) share many biological features, the different tissue origins can be mirrored by variations in their secretory profile, and in particular in the secreted extracellular vesicles (EVs). In this study, we carried out a detailed and comparative characterization of middle-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Given the different types and abundance of proteins and RNAs in EVs derived from different MSCs, the selection of tissue-specific MSCs should be based on the pathological characteristics of diseases. According to available studies, ADSCs-derived EVs contained high levels of proangiogenic factors, BMSCs-derived EVs enriched with prodifferentiation and chemotactic proteins, and EVs secreted by hUCMSCs exhibited strong anti-inflammatory effects (Gorgun et al, 2021;Gupta et al, 2022). Therefore, further studies are warranted to elucidate the specific effects of different sources of MSC-EVs on various physiological processes and their strength, to guide application in disease therapy.…”
Section: Research Hotspots and Future Trendsmentioning
confidence: 99%
“…Given the different types and abundance of proteins and RNAs in EVs derived from different MSCs, the selection of tissue-specific MSCs should be based on the pathological characteristics of diseases. According to available studies, ADSCs-derived EVs contained high levels of proangiogenic factors, BMSCs-derived EVs enriched with prodifferentiation and chemotactic proteins, and EVs secreted by hUCMSCs exhibited strong anti-inflammatory effects (Gorgun et al, 2021;Gupta et al, 2022). Therefore, further studies are warranted to elucidate the specific effects of different sources of MSC-EVs on various physiological processes and their strength, to guide application in disease therapy.…”
Section: Research Hotspots and Future Trendsmentioning
confidence: 99%
“…In vitro studies by co-culturing ADSCs and chondrocytes showed an increased secretion of many growth factors and cytokines, such as epidermal growth factor (EGF), vascular endothelial growth factor (VEGF), transforming growth factor beta (TGF-β), and bone morphogenetic protein 2 (BMP-2) of ADSCs, which in turn stimulated the synthesis of cartilage ECM ( Zhong et al, 2016 ). ADSCs-derived EVs contain functional proteins and RNAs, such as DKK-1, versican, annexin A1, and miR-100-5p, which could induce chondrogenesis and reduce inflammation ( Tofiño-Vian et al, 2018 ; Wu et al, 2019 ; Giannasi et al, 2020 ; Gorgun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVs were separated from P3 regularly fed cells as follows: sub-confluent hBM-MSC cultured in SFM were washed three times in PBS and cultured in basal medium (αMEM, Gibco) for 72 h. Conditioned medium (CM) was harvested after 72 h and processed immediately through two subsequent centrifugation steps [ 33 ]. This clarified CM was differentially ultra-centrifuged (Optima XPN-100, Beckman-Coulter, Brea, CA, USA) at 10,000× g for 40 min at 4 °C and, subsequently, twice at 100,000× g for 2 h at 4 °C to pellet EVs [ 33 ]. EVs were resuspended in PBS and stored at −80 °C for further experiments or until in vivo injection.…”
Section: Methodsmentioning
confidence: 99%